Transformative, interdisciplinary and intercultural learning for developing HEI students’ sustainability-oriented competences: a case study - Sommier, Mélodine; Wang, Yijing; Vasques, Ana (Environment, development and sustainability, 2022)
The literature has produced relevant theoretical insights into pedagogical frameworks, tools and competences that would be best suited to teach sustainability at higher education (HE). This article contributes to such a discussion using a course on sustainability developed by us as a case study. Two research questions are tackled in this article: (1) How to empower students to address urban sustainability challenges through the inclusion of transformative, interdisciplinary and intercultural learning into the current HE system? (2) Which pedagogical tools can be used to develop students’ sustainability-oriented competences? To address the research questions, the case study consists of two parts. First, by reflecting on the course design, this article aims to shed light on the benefits and challenges of transformative pedagogy and of an interdisciplinary and intercultural framework. Second, by analyzing students’ learning diaries ( N = 36) using thematic analysis, this article offers insights into some of the students’ learning process, allowing us to assess the strengths and weaknesses of the course design as well as draw implications to improve and renew courses on sustainability in HE. The findings from the learning diaries indicate the students’ thirst for formal knowledge on sustainability, which they connected to their professional development and yearning for action. The learning diaries also suggest students’ increasing awareness of sustainability as a systemic and structural issue during the course, which aligns with the transformative learning framework used. Finally, this study emphasizes the need for structural support to meaningfully integrate sustainability in HE curricula and teaching practices.